FREQUENCY OF NEOPLASMS IN CANINE MAMMARY GLAND: RETROSPECTIVE STUDY IN THE PERIOD 1992-2006 IN LIMA, PERU - Chau V., Guillermo (2013)
The aim of the study was to determine the frequency of neoplasms in the mammary gland of dogs. In this retrospective study (period of 1994-2006), records from the Patology Laboratory of the Veterinary Medicine Faculty, San Marcos University were used. There were a total of 4496 canine protocols of which 1128 were corresponded to neoplasms (25 ± 1.2%). Among them, 204 cases were in the mammary gland (18.1 ± 2.3%). Mammary neoplasms gland mainly occurred in females (94%) and in crossbred animals (38.3%). Dogs older than 10 years of age were most affected (46.4%). The inguinal pair was also the most affected (32.6%). Malignant neoplasms were more frequent (78%) than benign neoplasms. The adenocarcinoma was the most common neoplasm affecting the mammary gland (53.4%).